The Effect of Village Fund Allocation Assistance (ADD) on Seaweed Farmer's Income in Langere Village Bonegunu District North Buton Regency - Enci Safira; Rosmawaty Rosmawaty; Syamsul Alam Fyka (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
Seaweed cultivation is one type of aquaculture in the field of fisheries that has the opportunity to be developed in Indonesian waters. Efforts to increase fishery production can be achieved through aquaculture on land and at sea. Seaweed is one of the sources of accelerated growth in the agricultural sector due to the elastic nature of its demand for income. The rate of population growth accompanied by an increase in revenue and the development of industrial centers are potential factors for increasing demand for seaweed products. Through many requests for seaweed products from the company, seaweed farming communities work hard to produce large harvests. Through many requests for seaweed products from the company, seaweed farming communities work hard to make large harvests. This study aims to determine the effect of village fund allocation assistance on the income of seaweed farmers (whether aid is right on target or not). Respondents used a simple random sampling method to select the sample of seaweed farmers. The sample in this study was 31 seaweed farmers. The results in this study indicate that the Village Fund Allocation Assistance shows a positive influence at a level of 0.05 on the income of seaweed farmers. The regression coefficient for Village Fund Allocation assistance is 1.452, with a significance level of 0.000. Where the significance value is smaller than the real level (0.05), the Village Fund Allocation assistance significantly influences the income of seaweed farmers in Langere Village, Bonegunu District, North Buton Regency